Rural‐Urban Differences in Human Papillomavirus‐associated Cancer Trends and Rates. Issue 2 (28th May 2018) - Zahnd, Whitney E.; Rodriguez, Christofer; Jenkins, Wiley D.
Abstract: Purpose: Human papillomavirus (HPV) is the most prevalent sexually transmitted disease and a known cause of many cancers. Previous research explored HPV‐associated (HPVa) cancer differences by gender or race, but rural‐urban differences in rates and trends have received little attention. This study examined rural‐urban differences in rates and temporal trends for individual HPVa cancers. Methods: The North American Association of Central Cancer Registries public use data set, representing approximately 93% of the US population, was used to calculate age‐adjusted incidence rates and rate ratios (RR; 2009‐2013) and overall and annual percentage changes (APC; 1995‐2013) for HPVa cancers, including cervical carcinomas and squamous cell carcinomas of the vagina, vulva, penis, anus, rectum, and oropharynx. Rural‐Urban Continuum Codes were dichotomized into urban (levels 1‐3) and rural (4‐9). RRs and APC analyses were stratified by cancer site, rurality, gender, and race/ethnicity. Findings: Combined HPVa cancers were elevated in rural populations compared to urban (RR = 1.07; 95% CI = 1.06‐1.09). Rural females had significantly higher rates of cervical, vaginal, vulvar, oropharyngeal, and anal cancer compared to their urban peers, while rural males had higher rates of penile cancer. Many disparities remained after racial/ethnic stratification (eg, white and black rural females were at increased risk of cervical carcinoma). Regarding trends, rural females and males experienced greater rate increases, or smaller rate decreases, overall and by APC, for nearly every cancer site. Conclusions: Rural populations experience consistent disparities in HPVa cancers. Further research should examine contributing behavioral and epidemiological risk factors and interventions to improve HPV vaccination.